Model Pendidikan Pesantren Inklusif bagi Anak Berkebutuhan Khusus: Studi Kasus Pesantren Al-Achsaniyyah Kudus - Putri Nurina; Sarwenda (El-Athfal: Jurnal Kajian Ilmu Pendidikan Anak, 2026)
Less than 0.1% of more than 42,000 Islamic boarding schools (pesantren) in Indonesia serve children with special needs, creating a sharp service gap amid the projected 2.9 million autistic children by 2030. This study analyzes the inclusive pesantren model at Pesantren Al-Achsaniyyah Kudus, a pioneer institution since 2007. Using a qualitative instrumental case study approach, data were collected through intensive participatory observation, in-depth interviews with 31 informants including caregivers, teachers, therapists, parents, and alumni, as well as analysis of various internal pesantren documents. The study identifies six main components of the inclusive pesantren model. First, the pesantren admits students with various diagnoses, of which 62.6% are autistic, along with ADHD and Down syndrome. Second, an adaptive curriculum is developed based on three independence domains: self-care, worship, and talent development. Third, teaching strategies integrate ABA and TEACCH approaches through short instructions, positive reinforcement, prompting-fading techniques, and the use of visual schedules. Fourth, a 24-hour habitual learning program produces significant outcomes: 98% of advanced-level students achieve full independence, 89% of intermediate-level students require only minimal assistance, and 60% of basic-level students show meaningful improvement. Fifth, tripartite collaboration among the pesantren, therapists, and parents is actively maintained. Sixth, the pesantren provides special needs-friendly facilities. The success of this model can be explained through the synthesis of Vygotsky's Zone of Proximal Development, Bandura's social learning theory, and Lovaas's ABA principles. Based on these findings, this study provides an evidence-based reference model for developing inclusive pesantren in Indonesia.